CORRELATION OF TOTAL LYMPHOCYTE COUNT WITH CD4 COUNT IN HIV/TB COINFECTED PATIENTS - Herniaty Rampo; Uleng Bahrun; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
HIV-TB co-infection is a global challenge in the healthcare world. HIV infection causes CD4 to decrease which has a role in TB immunity. CD4 as a marker for HIV progression have expensive cost and not available in all healthcare facilities, so WHO recommended TLC as a substitute for CD4. This study aims to determine the correlation of TLC and CD4 in HIV-TB co-infection patients.This was a retrospective study using medical records of hospitalized patients with HIV-TB co-infection in Dr.Wahidin Sudirohusodo Hospital. The correlation was analyzed by Spearman test. CD4 data were divided into two groups: CD4 < 200 cells/mm3 and CD4 ≥ 200 cells/mm3 and Mann-Whitney test was performed. Data were also analyzed by ROC curve.In total 172 data with diagnosis of HIV-TB co-infection, Spearman test showed a positive correlation between TLC and CD4 with moderate correlation strength (p <0.001 and r = 0.56). Mann-Whitney test showed a significant difference between CD4 < 200 cells/mm3 and CD4 ≥ 200 cells/mm3 (p < 0.001). ROC curve analysis showed that TLC has a good accuracy value for predicting CD4 in CD4 < 200 cells/mm3 (AUC = 0.911). Sensitivity 88.9% with specificity 84.7% was found in TLC 1154.9 cells/mm3 which predicted CD4 < 200 cells/mm3.There was a positive correlation between TLC and CD4 with moderate correlation strength. TLC can predict CD4 in CD4 <200 cells/mm3. We suggest further studies on patients who receive drug therapy.